(untitled) (Research, Society and Development, 2022)
Objective: To describe the profile of mortality from leishmaniasis in Brazil. Methods: Descriptive study using data from records of death certificates in the Mortality Information System (SIM) from 2015 to 2019. Data were collected and systematized using Microsoft Excel 2016. Results: Over the period, 1,748 deaths from leishmaniasis were reported in Brazil. Regarding region/unit of the federation, the Northeast had the highest record of deaths with 56.2% of cases, highlighting the state of Maranhão (18.8%). In relation to the Mortality Rate (deaths per 100,000 inhabitants), it was identified that the states with the highest values are located in the North and Northeast regions: Tocantins 1.39; Maranhão 1.21; Piauí 0.75; Para 0.62; and Ceará 0.56. In relation to age, there was a greater number among individuals between 50-59 years (14.9%). Regarding gender, 67.6% of deaths from leishmaniasis occurred in men. In addition, the disease mainly affected brown people (64.6%) and 21.3% of individuals had 1 to 3 years of schooling. Conclusion: Deaths from leishmaniasis occurred mainly in the north and northeast regions, aged 50-59, male, brown and with little or no education.